Medical Treatment in Coronary Patients: Is there Still a Gender Gap? Results from European Society of Cardiology EUROASPIRE V Registry - Vynckier, Pieter; Ferrannini, Giulia; Rydén, Lars; Tokgözoğlu, Lale; Bruthans, Jan; Kotseva, Kornelia; Wood, David; De Backer, Tine; Gevaert, Sofie; De Bacquer, Dirk; De Smedt, Delphine (Cardiovascular drugs and therapy, 2021)
PURPOSE: This study is aimed at investigating gender differences in the medical management of patients with coronary heart disease (CHD). METHODS: Analyses were based on the ESC EORP EUROASPIRE V (European Survey Of Cardiovascular Disease Prevention And Diabetes) survey. Consecutive patients between 18 and 80 years, hospitalized for a coronary event, were included in the study. Information on cardiovascular medication intake at hospital discharge and at follow-up (≥ 6 months to < 2 years after hospitalization) was collected. RESULTS: Data was available for 8261 patients (25.8% women). Overall, no gender differences were observed in the prescription and use of cardioprotective medication like aspirin, beta-blockers, and ACE-I/ARBs (P > 0.01) at discharge and follow-up respectively. However, a statistically significant difference was found in the use of statins at follow-up, in disfavor of women (82.8% vs. 77.7%; P < 0.001). In contrast, at follow-up, women were more likely to use diuretics (31.5% vs. 39.5%; P < 0.001) and calcium channel blockers (21.2% vs. 28.8%; P < 0.001), whereas men were more likely to use anticoagulants (8.8% vs. 7.0%; P < 0.001). Overall, no gender differences were found in total daily dose intake (P > 0.01). Furthermore, women were less likely than men to have received a CABG (20.4% vs. 13.2%; P < 0.001) or PCI (82.1% vs. 74.9%; P < 0.001) at follow-up. No gender differences were observed in prescribed (P = 0.10) and attended (P = 0.63) cardiac rehabilitation programs. CONCLUSION: The EUROASPIRE V results show only limited gender differences in the medical management of CHD patients. Current findings suggest growing awareness about risk in female CHD patients.
Keywords: Sex Factors; Patient Care Management; Humans; Coronary Artery Bypass; lidé středního věku; Female; zdraví - znalosti, postoje, praxe; lidé; Europe; hospitalizace; kardiovaskulární rehabilitace; sexuální faktory; kardiovaskulární látky; ženské pohlaví; Hospitalization; Middle Aged; koronární bypass; sekundární prevence; koronární nemoc; Coronary Disease; Women's Health; Practice Patterns, Physicians'; zdraví žen; lékařská praxe - způsoby provádění; Cardiovascular Agents; Health Knowledge, Attitudes, Practice; management péče o pacienta; Evropa; Cardiac Rehabilitation; Secondary Prevention